1999
DOI: 10.1074/jbc.274.24.17049
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Haploid Germ Cell-specific Nuclear ProteinKinase (Haspin) in Spermatid Nuclei and Its Effects on Somatic Cells

Abstract: We have cloned the entire coding region of a mouse germ cell-specific cDNA encoding a unique protein kinase whose catalytic domain contains only three consensus subdomains (I-III) instead of the normal 12. The protein possesses intrinsic Ser/Thr kinase activity and is exclusively expressed in haploid germ cells, localizing only in their nuclei, and was thus named Haspin (for haploid germ cell-specific nuclear protein kinase). Western blot analysis showed that specific antibodies recognized a protein of M r 83,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
2
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 41 publications
8
113
2
14
Order By: Relevance
“…This particular application of our method would break the boundary between germ and somatic cells, and open a new phase in germ cell research. 18 , Gsg2/Haspin-GFP 23 , and Acr-GFP [21][22] , were used to produce GS cells. The pCXN-GFP mice were provided by Dr. Okabe, Gsg2/Haspin-GFP mice were provided by Dr. Tanaka, and Acr-GFP mice were provided by RIKEN BRC through the National Bio-Resource Project of MEXT, Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular application of our method would break the boundary between germ and somatic cells, and open a new phase in germ cell research. 18 , Gsg2/Haspin-GFP 23 , and Acr-GFP [21][22] , were used to produce GS cells. The pCXN-GFP mice were provided by Dr. Okabe, Gsg2/Haspin-GFP mice were provided by Dr. Tanaka, and Acr-GFP mice were provided by RIKEN BRC through the National Bio-Resource Project of MEXT, Japan.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that GS cells are able to proceed up to or beyond the meiotic phase of spermatogenesis, we exploited 2 lines of transgenic mice, Acr-GFP 21,22 and Gsg2-GFP 23 , to establish GS cells from them. We confirmed that the GS cells derived from Acr-GFP (Acr-GS cells) and Gsg2-GFP (Gsg2-GS cells) expressed GFP at the expected phases of differentiation, mid-and end-meiotic, respectively, when transplanted in the testis in vivo (data not shown).…”
Section: Colonization Of Injected Gs Cells In Cultured Tissuesmentioning
confidence: 99%
“…The coded protein localizes in the nucleus of germ cells and showed kinase activity. It was subsequently renamed haploid germ cell-specific nuclear protein kinase (Haspin) [4]. Haspin mRNA is found in diploid cells of many proliferative tissues such as testis, thymus, bone marrow, and spleen as well as in many proliferative cell lines [5][6][7].…”
Section: Discoverymentioning
confidence: 99%
“…So far, the precise cellular localization of the endogenous protein could not be determined due to lack of immunofluorescence-specific antibodies to Haspin. However, several overexpression studies have reported localization of GFP-or Myc-tagged Haspin in different eukaryotic cell lines (HeLa, U-2 OS, Hek293, COS-7) using time-lapse video microscopy or immunofluorescence staining techniques or time-lapse video microscopy [4,13]. All these studies showed that Haspin localizes in discrete foci and nucleoli in the nucleus during interphase.…”
Section: Haspin Localizationmentioning
confidence: 99%
See 1 more Smart Citation